Our Journey Beyond Sunset Boulevard Evidence-based Analysis of Tumor-Targeted Gene- and Immuno-Therapies Shine a Critical Spotlight on "True" Long-Term Cancer-Free Survival - Gordon, Erlinda M.; Hall, Frederick L. (IntechOpen, 2021)
The revival of DeltaRex-G (formerly Rexin-G)-the first proactive tumor-hunting/tumor-killing biomedicine of this kind in history-returned active tumor surveillance and a precision-guided "silver bullet" (dnG1 killer gene) to the cancer clinic with "Expanded Access" in 2019. Empowered by US Right-to-Try legislation, while honoring ethical principles of "informed consent," this unique graphic/picturesque presentation of clinical and translational medicine is intended for postmodern (post-Enlightenment) layman readers, including cancer patients, students, researchers, and future practitioners in the field of precision gene-based medicine. Confronting logical fallacies in popular opinion, the authors present newsworthy, up-to-date clinical research documenting the successful management of refractory metastatic cancers with tumor-targeted gene therapy vectors-validating "pathotropic" (disease-seeking) tumor targeting avant la lettre.